Enzymes in the hypopharyngeal gland extracts from workers of Scaptotrigona postica (Hymenoptera, Apinae, Meliponini) related to food storing in the colony - Costa, Rosiléia A. C. [UNESP]; Da Cruz-Landim, Carminda [UNESP] (My University, 2002)
This study reports on research of enzymes produced by the hypopharyngeal glands, which are related to food storing in the colony, from gland extracts from nurse and forager workers of S. postica. Only the presence of the saccharase was detected in the extracts from the glands of forager workers. The results were compared to the enzymatic content of similar extracts of A. mellifera taking into account the behavioral differences among the two species.
Keywords: Amylase; Enzymes; Glucose oxidase; Hypopharyngeal glands; Meliponines; Saccharase; Stingless bees; Workers; Apis mellifera